Problematika Buruh Perempuan (Studi atas Strategi Survive Perempuan sebagai Buruh Kebun PTP XII Desa Sempol Kecamatan Sempol Kabupaten Bondowoso): Problems of Female Laborers (A Study on Survival Strategies of Women as Plantation Workers at PTP XII in Sempol Village, Sempol District, Bondowoso Regency) - Mahrus Mahrus (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2013)
A complex poverty problem requires global and coordinated attention from all components. It is connected with the poverty issues of society, especially the people of Sempol, whose income mostly comes from working in the coffee and strawberry fields of PTP XII. The method used in this research not only describes poor women but also aims to uncover the meaning behind poverty. This research employs a qualitative method conversed with the symbolism paradigm. The study concludes that the majority of women in Sempol Village have a dual role as workers and housewives responsible for household chores and child-rearing. Being a dual-role woman is not easy. Several problems arise and must be faced by these women. The efforts they make while working outside as plantation workers at PTPN XII to address childcare issues include utilizing their limited time to provide guidance and advice as much as possible. To care for their children, they are assisted by school teachers in the morning and religious teachers in the afternoon. Furthermore, some women also rely on siblings or other relatives to take care of their children. Masalah kemiskinan yang kompleks membutuhkan perhatian global dan terkoordinasi dari semua komponen. Hal ini terkait dengan masalah kemiskinan masyarakat, terutama masyarakat Sempol yang sebagian besar pendapatannya berasal dari pekerjaan di kebun kopi dan stroberi PTP XII. Metode yang digunakan dalam penelitian ini tidak hanya mendeskripsikan perempuan miskin, tetapi juga ingin mengungkap makna di balik kemiskinan. Penelitian ini menggunakan metode kualitatif yang berparadigma simbolisme. Dari penelitian disimpulkan bahwa mayoritas perempuan di Desa Sempol memiliki peran ganda, yaitu sebagai pekerja dan ibu rumah tangga yang bertanggung jawab atas rumah tangga dan pengasuhan anak. Menjadi perempuan berperan ganda bukanlah hal yang mudah. Ada beberapa masalah yang muncul dan harus dihadapi oleh perempuan tersebut. Upaya yang mereka lakukan saat bekerja di luar sebagai buruh kebun di PTPN XII dalam menghadapi masalah pengasuhan anak adalah dengan memanfaatkan waktu terbatas mereka untuk memberikan bimbingan dan nasihat sebisa mungkin. Untuk mengurus anak-anak mereka, mereka dibantu oleh guru sekolah di pagi hari dan guru agama di sore hari. Selain itu, sebagian perempuan juga memanfaatkan saudara atau kerabat lainnya untuk mengurus anak-anak mereka.